Nigeria and Russian Economic Relations: The Post-Cold War Experience - NWOKOLOBIA, Anthony C. (International Journal of Public Administration Studies, 2024)
Post-Soviet Russia pursues very difficult foreign policy objectives in its relations with African states and in doing so it often draws on the relationships, partnerships, and formal and informal networks forged during the Cold War. Russia has abandoned its promotion of socialism to pursue crude economic interests via its business elite, based on values that appear to be in stark contrast to the conventions of Western liberalism. Undoubtedly, the Nigeria-Russia bilateral relations during the Post Cold War have had both good and difficult experience. This study therefore is an assessment of the Nigeria and Russia economic ties from the historical point of view relying on traditional diplomatic theory as a tool to trace the existing diplomatic ties between the two countries. In conclusion, Nigeria-Russia relations have come of age, despite some psychological differences and suspicions, there are lots of gains and work is still needed to be done in the direction of media and cultural exchanges and some trade favorable policies on the part of Russian government to allow more Nigerian exports, while it is desirable that Nigeria and Russia move their bilateral relation to a new level of active cooperation in important and strategic economic sectors. The study therefore recommends among others that the economic relations between the two countries should be strengthening and make more emphasis than before on the development of cooperation at the level of small and middle-size enterprises.